Manufacturing urbanism: Improvising the urban–industrial nexus through Chinese economic zones in Africa. (May 2022) - Goodfellow, Tom; Huang, Zhengli
The relationship between industrialisation and urban development is subject to assumptions based on experiences in the global North, with little research on how it plays out in countries undergoing urbanisation and industrialisation today. In the context of recent excitement about China's role in stimulating an 'industrial revolution' in Africa, we examine how Chinese zones in Ethiopia and Uganda are influencing the urban–industrial nexus. We argue that Chinese zones are key sites of urban–industrial encounter, but these dynamics are not primarily driven by the government officials that dominate the 'policy mobilities' literature, nor by the State-Owned Enterprises usually associated with Chinese activity overseas. Rather, they are emerging through the activities of inexperienced private Chinese actors who do not even operate in the worlds of urban policy. Faced with government histories and capacities that vastly differ from China's, directly replicating the Chinese experience is virtually impossible; yet the tentative and improvisational relationships between Chinese firms, African government authorities and other local actors are gradually moulding new urbanisms into shape. The piecemeal bargaining and negotiation that unfolds through these relationships bridges some of the gaps between industrialisation and planning, but this cannot compensate for the governance of the urban–industrial nexus at higher scales.